TEACHING RECOUNT PARAGRAPH WRITING BY USING WH - QUESTIONS TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 2 SUHAID - Lassa, Merry Susanti (West Kalimantan Scholars: Studies on English Language and Education, 2014)
The objective of this study was to find out the effectiveness of the use WH-Questions and to find out the significant effectiveness of teaching writing recount paragraph through the use of WH-Questions to the eighth grade students of SMPN 2 Suhaid in academic year 2013/2014. This research was pre-experimental research and used one group of pretest and posttest design. The sample was chosen by using cluster sampling. There were 34 students from 2 classes as the population, while 17 students were taken from class A as the sample. The data was collected by measurement technique in the form of written test. Based on the findings, it was found that teaching recount paragraph writing by using WH-Questions was effective. The effectiveness of WH-Questions technique was analyzed by effect size formula, thus it was categories as high influence. Then, the result of t-test computation is higher than t-table. It means that the null hypothesis (Ho) is rejected and the alternative hypothesis is accepted. Therefore, the researcher recommends that the use of WH-Questions technique can be an alternative way to teach writing, especially in teaching recount paragraph writing. This result hopefully would motivate teachers to use WH-Questions to teach writing in their classroom.